Intraluminal gas escape from biopsy valves and endoscopic devices during endoscopy: caution advised during the COVID-19 era - Urakawa, Shinya; Hirashita, Teijiro; Momose, Kota; Nishimura, Makoto; Nakajima, Kiyokazu; Milsom, Jeffrey W. (Endoscopy International Open, 2021)
Background and study aims The risk of aerosolization of body fluids during endoscopic procedures should be evaluated during the COVID-19 era, as this may contribute to serious disease transmission. Here, we aimed to investigate if use of endoscopic tools during flexible endoscopy may permit gas leakage from the scope or tools.Material and methods Using a fresh 35-cm porcine rectal segment, a colonoscope tip, and manometer were placed intraluminally at opposite ends of the segment. The colonoscope handle, including the biopsy valve, was submerged in a water bath. Sequentially, various endoscopic devices (forceps, clips, snares, endoscopic submucosal dissection (ESD) knives) were inserted into the biopsy valve, simultaneously submerging the device handle in a water bath. The bowel was slowly inflated up to 74.7 mmHg (40 inH2O) and presence of gas leakage, leak pressure, and gas leakage volume were measured.Results Gas leakage was observed from the biopsy valve upon insertion and removal of all endoscopic device tips with jaws, even at 0 mmHg (60/60 trials). The insertion angle of the tool affected extent of gas leakage. In addition, gas leakage was observed from the device handles (8 of 10 devices) with continuous gas leakage at low pressures, especially two snares at 0 mmHg, and an injectable ESD knife at 0.7 ± 0.8 mmHg). Conclusions Gas leakage from the biopsy valve and device handles commonly occur during endoscopic procedures. We recommend protective measures be considered during use of any tools during endoscopy.